Does the diurnal increase in central temperature interact with pre-cooling or passive warm-up of the leg? - Racinais, S.; Blonc, S.; Oksa, J.; Hue, O. (Journal of Science and Medicine in Sport, 2009)
Seven male subjects volunteered to participate in an investigation of whether the diurnal increase in core temperature influences the effects of pre-cooling or passive warm-up on muscular power. Morning (07:00-09:00 h) and afternoon (17:00-19:00 h) evaluation of maximal power output during a cycling sprint was performed on different days in a control condition (room at 21.8 °C, 69% rh), after 30 min of pre-cooling in a cold bath (16 °C), or after 30 min of passive warm-up in a hot bath (38 °C). Despite an equivalent increase from morning to afternoon in core temperature in all conditions (+0.4 °C, P < 0.05), power output displayed a diurnal increase in control condition only. A local cooling or heating of the leg in a neutral environment blunted the diurnal variation in muscular power. Because pre-cooling decreases muscle power, force and velocity irrespective of time-of-day, athletes should strictly avoid any cooling before a sprint exercise. In summary, diurnal variation in muscle power output seems to be more influenced by muscle rather than core temperature.